Mapping global evidence on strategies and interventions in neurotrauma and road traffic collisions prevention: a scoping review - Santhani M Selveindran; Tamara Tango; Muhammad Mukhtar Khan; Daniel Martin Simadibrata; Peter J. A. Hutchinson; Carol Brayne; Christine Hill; Franco Servadei; Angelos G. Kolias; Andres M. Rubiano; Alexis J. Joannides; Hamisi K. Shabani (Systematic Reviews, 2020)
Abstract Background Neurotrauma is an important global health problem. The largest cause of neurotrauma worldwide is road traffic collisions (RTCs), particularly in low- and middle-income countries (LMICs). Neurotrauma and RTCs are preventable, and many preventative interventions have been implemented over the last decades, especially in high-income countries (HICs). However, it is uncertain if these strategies are applicable globally due to variations in environment, resources, population, culture and infrastructure. Given this issue, this scoping review aims to identify, quantify and describe the evidence on approaches in neurotrauma and RTCs prevention, and ascertain contextual factors that influence their implementation in LMICs and HICs. Methods A systematic search was conducted using five electronic databases (MEDLINE, EMBASE, CINAHL, Global Health on EBSCO host, Cochrane Database of Systematic Reviews), grey literature databases, government and non-government websites, as well as bibliographic and citation searching of selected articles. The extracted data were presented using figures, tables, and accompanying narrative summaries. The results of this review were reported using the PRISMA Extension for Scoping Reviews (PRISMA-ScR). Results A total of 411 publications met the inclusion criteria, including 349 primary studies and 62 reviews. More than 80% of the primary studies were from HICs and described all levels of neurotrauma prevention. Only 65 papers came from LMICs, which mostly described primary prevention, focussing on road safety. For the reviews, 41 papers (66.1%) reviewed primary, 18 tertiary (29.1%), and three secondary preventative approaches. Most of the primary papers in the reviews came from HICs (67.7%) with 5 reviews on only LMIC papers. Fifteen reviews (24.1%) included papers from both HICs and LMICs. Intervention settings ranged from nationwide to community-based but were not reported in 44 papers (10.8%), most of which were reviews. Contextual factors were described in 62 papers and varied depending on the interventions. Conclusions There is a large quantity of global evidence on strategies and interventions for neurotrauma and RTCs prevention. However, fewer papers were from LMICs, especially on secondary and tertiary prevention. More primary research needs to be done in these countries to determine what strategies and interventions exist and the applicability of HIC interventions in LMICs.